Systematic literature on the effectiveness of government public relations: the public perspective / Muhammad Rusyaidi Mohammad Rafie … [et al.] - Mohammad Rafie, Muhammad Rusyaidi; Ilyas, Ilya Yasnoriza; Sultan Mohideen, Rosilawati; Amairudin, Muhammad Firdaus; Jaapar, Iqbal (Faculty of Communication & Media Studies, 2022)
Government Public Relations Practitioner should make sure people agree on government-run services and help people communicate what they want from the government. Plus, Government Public Relations Practitioner is also important to ensure people are continuously aware of the government's concerns, challenges and actions. However, most of Malaysians still don’t know much about the existence of Government Public Relations in every government sectors. One of the questions that need to be addressed is how to measure the public perspective towards the practice of Government Public Relations. Therefore, this research will analyze the public perspective towards the practice of Government Public Relations and the use of social media by them. There were 14 journals were chosen after reaching full requirements of the criteria. Results showed that Government Public Relations are receiving negative perspective from public because not a necessary in an organization, lack of knowledge and not fully utilized social media. However, they see the use of social media can enhance and restore public trust towards Government Public Relations.